Communication partner perspectives of aphasia self-management and the role of technology: an in-depth qualitative exploration. Issue 23 (6th November 2022) - Nichol, Leana; Wallace, Sarah J.; Pitt, Rachelle; Rodriguez, Amy D.; Hill, Annie J.
Abstract: Purpose: "Self-management" empowers individuals to take responsibility for their healthcare through skill-building, personal growth, and self-efficacy related to chronic health condition management. Self-management approaches may benefit people with aphasia (PwA); however, PwA are often excluded from stroke self-management research and there is no published research reporting on aphasia-specific self-management programs. Communication partners (CPs) are involved in the rehabilitation and day-to-day lives of PwA, thus giving them unique insights and knowledge of PwA needs. The present study aimed to investigate CP experiences and perspectives regarding aphasia self-management and to explore CP perceptions of the use of technology in aphasia self-management. Methods: In-depth, semi-structured interviews with 14 CPs living in Australia. Interview data was analysed using qualitative content analysis. Results: Analysis revealed six core themes: (1) aphasia self-management is embedded into everyday life, (2) CPs provide comprehensive self-management support, (3) speech-language pathologists (SLPs) provide tools and support to enable PwA to self-manage, (4) aphasia self-management can be enhanced by technological supports, (5) potential positive outcomes of aphasia self-management, and (6) factors influencing successful aphasia self-management. Conclusions: Aphasia self-management programs should focus on individual needs, functional communication in daily life, and social interaction. PwA and CPs are central to these programs, assisted by SLPs. Technology should be explored to augment aphasia self-management. Implications for Rehabilitation: Communication partners suggest that people with aphasia are already engaging in aspects of self-management and that more formal aphasia-specific self-management approaches may be beneficial. Dedicated aphasia self-management programs should be situated in daily life with a focus on functional communication, life participation, confidence, and independence. Communication partners, speech-language pathologists, and technology are key support sources for aphasia self-management. Further input should be sought from communication partners in the development of aphasia self-management programs.